2010
DOI: 10.1186/1475-2859-9-89
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of the extreme thermophile Caldicellulosiruptor saccharolyticus: an efficient hydrogen cell factory

Abstract: Global concerns about climate changes and their association with the use of fossil fuels have accelerated research on biological fuel production. Biological hydrogen production from hemicellulose-containing waste is considered one of the promising avenues. A major economical issue for such a process, however, is the low substrate conversion efficiency. Interestingly, the extreme thermophilic bacterium Caldicellulosiruptor saccharolyticus can produce hydrogen from carbohydrate-rich substrates at yields close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 120 publications
2
60
0
Order By: Relevance
“…Based on previous knowledge, the main concerns when designing DF using C. saccharolyticus are the sensitivity of this thermophile to elevated levels of H 2aq and osmotic pressure [3,18]. In addition, inhibitors in the wheat straw hydrolysate may affect the fermentation profile.…”
Section: Verification Of the Df Model And The Effect Of Spargingmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous knowledge, the main concerns when designing DF using C. saccharolyticus are the sensitivity of this thermophile to elevated levels of H 2aq and osmotic pressure [3,18]. In addition, inhibitors in the wheat straw hydrolysate may affect the fermentation profile.…”
Section: Verification Of the Df Model And The Effect Of Spargingmentioning
confidence: 99%
“…In a conventional dark fermentation (DF) process only about 7.5e15% of the energy contained in glucose is converted to H 2 (corresponding to a yield of 1e2 mol H 2 per mole glucose the rest of the energy is contained in volatile fatty acids (VFA)) [2]. Fortunately, recent progress in the characterisation of new potential organisms has revealed a number of organisms providing better H 2 yields [3]. Caldicellulosiruptor saccharolyticus, is one such organism, and is able to produce almost the theoretical maximum yield of 4 mol H 2 per mole glucose [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variants of Caldicellulosiruptor saccharolyticus (Herbel et al, 2010;Willquist et al, 2010) and Thermotogoelfii (de Vrije et al, 2009;Schut and Adams, 2009;Nguyen et al, 2010) show particular promise as organisms able to mediate the conversion of organic compounds to hydrogen. Hydrogen capacities of the archaeal genera Thermococcus and Pyrococcus (Silva et al, 2000;Kanai et al, 2005), and bacterial strains belonging to the genera Thermoanaerobacter and Thermotogales (Nandi and Sengupta, 1998;Nandi et al, 2001;Bagi et al, 2007;Shaw et al, 2008a) have been reported.…”
Section: Thermophiles and Gaseous Fuels: Methane And Hydrogenmentioning
confidence: 99%
“…1) (Chang and Yao, 2011;Demain et al, 2005;Lin et al, 2011;Taylor et al, 2009). Moreover, TGPAs, such as Caldicellulosiruptor saccharolyticus, are capable of producing hydrogen from lignocellulosic and waste materials (Willquist et al, 2010).…”
Section: Introductionmentioning
confidence: 99%